Analisis Social Media Marketing Activities dalam Meningkatkan Niat Pembelian dengan Peran Mediasi Brand Image dan Brand Trust (NJS Project) - Ni Wayan Sriastini; Utami, Made Ayu Jayanti Prita; Hapsari, Yulia Tria (Jurnal Bisnis dan Kewirausahaan, 2025)
This study is motivated by the increasing significance of social media as a strategic marketing channel within the online florist sector, as illustrated by NJS Projects in Denpasar, which actively utilizes Instagram to engage its audience. The objective of this research is to investigate the influence of Social Media Marketing Activities (SMMA) on consumers’ online purchase intentions, with Brand Image and Brand Trust serving as mediating variables. Employing a quantitative research approach, data were gathered through a survey of 110 respondents who are active followers of the @njs.projects Instagram account, and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings indicate that SMMA significantly contributes to strengthening brand image and building consumer trust, which in turn positively affects online purchase intention. This research provides practical implications for businesses seeking to optimize their digital marketing efforts and adds to the growing academic literature on digital marketing strategy.